ANALISIS KEBUTUHAN LUASAN HUTAN KOTA BERDASARKAN PENYERAPAN CO2 ANTROPOGENIK DI KOTA KUPANG - Rozari, Philipi de; Suwari, Suwari (Bumi Lestari; Vol 12 No 2 (2012), 2012)
The main purpose of the research is to analyze the needs of urban forest in the Kupang City based on the sink of CO 2 anthropogenic. Primary data collected through field surveys and laboratory analysis of leaf samples using carbohydrate method. Case studies and literature are used to obtain secondary data from relevant agencies or literature, especially the results of studies with similar cases. The results showed that increasing emmission of CO 2 anthropogenic. Total emissions of CO 2 anthropogenic come from the use of fuel oil and gas and electricity consumption was 393,498.003 tons/year, in 2015 increased to 490,673.45 tons/year, and in 2025 reached 710,928.38 tons/year. Urban forest area in the city today in many forms of 969.35 ha or 5.38%, but from the region of the pure function as urban forest is only 177 ha or 0.98%. Based on the absorption of CO 2 , the needs of urban forest area in the city at this time are sufficient, but based on Government Regulation number 63/2002 that establishes urban forest land area of at least 10% of the area of ??the city, the area available has not yet qualified. CO 2 absorption of 9 tree species studied vary between tree species, depending on the mass of net carbohydrates, leaf area, and number of leaves per tree. Plants that have high the absorptive capacity of CO 2 are the jackfruit and the banyan tree with value of 453.95 and 428.48 kg/tree/year, respectively, while the lowest  is flamboyant with 0.12 kg/tree/year of CO 2 absorption.
Keywords: CO2 anthropogenic, green open space, kupang city, urban forest